Pembuatan Plastik Biodegradable dari Pati Singkong (Manihot esculenta) dan Cangkang Telur dengan Penambahan Gliserol sebagai Plasticizer - Rahma, Miftahul; Dewi, Ratni; Wijaya, Nanang Rahmat; Sari, Ratna (Politeknik Negeri Lhokseumawe, 2025)
The problem of conventional plastic waste, which if difficult to decompose process a serious threat to the environment. As a solution, this study aims to produce biodegradable plastic made from cassava starch (Manihot esculenta) and eggshell powder, with glycerol as a plasticizer. The addition of eggshell powder is intended to improve the mechanical properties of the plastic. Samples were prepared using varying amounts of glycerol (2; 2.5; 3.5; 3; 3.5; 4 mL) and eggshell powder (0.3; 0.6; 0.9; 1.2; 1.5 grams). The plastic was tested for biodegradability, tensile strength, functional group analysis (FT-IR), and surface morphology (SEM). The result showed that the sample with 0.3 grams of eggshell powder and 4 mL of glycerol had the highest biodegradation rate (98.94% within two days). The highest tensile strength (22.99 MPa) was achieved with 1.5 grams of eggshell powder and 4 mL of glycerol. FT-IR analysis identified the presence of carbonate, hydroxyl, carbonyl, and ester groups, while SEM observations revealed a surface morphology that was not fully homogeneous due to uneven particle dispersion. Overall, the resulting plastic meets the Indonesian National Standard (SNI) 7818:2016, particularly in terms of biodegradability.